Extracorporeal Cardiac Shock Wave Therapy Ameliorates Clinical Symptoms and Improves Regional Myocardial Blood Flow in a Patient with Severe Coronary Artery Disease and Refractory Angina. (20th August 2009) - Prinz, Christian; Lindner, Oliver; Bitter, Thomas; Hering, Detlef; Burchert, Wolfgang; Horstkotte, Dieter; Faber, Lothar
Abstract : Different therapeutic options are being used for chronic coronary artery disease (CAD). We report about a 51-year-old female with CAD and refractory angina pectoris despite maximally tolerated medical therapy and after both percutaneous coronary intervention (PCI) and coronary artery bypass grafting (CABG). The patient received cardiac shock wave therapy (CSWT) over a period of 6 month. There was no arrhythmia during or after treatment; enzyme levels were normal at all times. PET imaging showed a substantial improvement of myocardial stress perfusion. Since the patient reported that she now was fully capable to deal with her everyday life, further treatment options were postponed. Our case report suggests that ultrasound-guided CSWT is able to improve symptoms and perfusion in ischemic myocardium.